New firms - different jobs? An inquiry into the quality of employment in start-ups and incumbents - Andreas Koch; Jochen Späth (Institut für Angewandte Wirtschaftsforschung (IAW), 2009)
The present contribution addresses the question whether and how qualitative aspects of employmentlike weekly hours of work, wages or qualificationdiffer between new and established firms. Although a wide strand of literature in entrepreneurship research analyses the employment effects of start-ups vs. incumbent firms, our knowledge about differences in these qualitative aspects of employment is rather poor. Labour market research, on the other hand, has been thoroughly accounting for the consequences of technological and organisational change on the characteristics and turnover of jobs, but it rarely has been attempting to consider the relevance of firm entry. Based on the Establishment History Panel, a plant-level dataset constructed from employment information and comprising nearly the entire German economy, we find significant differences between new and incumbent firms with respect to employment quality. Surprisingly, the difference regarding the share of high-qualified labour isthough highly significantnot as high as commonly expected.
Keywords: J24; J31; J82; M13; 330; Start-ups; Employment; Quality of Employment; Germany; Establishment History Panel; Qualification; Wages; Part-Time; Marginal Employment; Arbeitsverhältnis; Qualifikation; Lohnstruktur; Ungeschützte Beschäftigung; Vergleich; Unternehmensgründung; Unternehmen; Deutschland